Simulation modeling of cAMP induced Dictyostelium aggregation by using object-oriented Pharo programming language - Nizheradze, K. A. (Biopolimery i kletka, 2020)
Aim. Periodically emitted spiral waves of cAMP determine the directed movement of individual amoebae of Dictyostelium discoideum towards the aggregation centers, which are the sources of these waves. Overall behavior of cell population that includes at this stage the thousands of independent organisms, could be reproduced and visualized through 2D simulation modeling. Methods. Object-oriented Pharo programming language was applied to create the model. As the source of random numbers the explicit inversive congruential generator was used. The following processes were attributed to developing population of individual amoebae: appearance of randomly distributed initial cells/spores; the search of feeding substrate; mitosis; forming (depending on the local environment) of the active aggregation centers; periodical emittances of cAMP spiral waves from the aggregation centers; directed movement of the amoebae, which were captured by the cAMP wave, towards aggregation center. Results. In course of the simulation of the feeding and subsequent mitosis, small initial population of amoebae was multiplied and distributed in the borders of specified area. When reaching a finite population density, the appearance of few active aggregation centers took place. Spiral cAMP waves periodically propagated from these centers in 2D area of the model. The cells, which were “covered” by the wave, begun their movement to the corresponding aggregation center, intermitted with the periods of the rest. During migration, the cells formed the characteristic “streams”. Conclusion. This model could provide additional important information in the study of the phases and underlying mechanisms of self-organizing cell populations.